Human immunodeficiency virus type 1 (HIV-1) strains selected for resistance against the HIV-1-specific [2',5'-bis-O-(tert-butyldimethylsilyl)-3'-spiro- 5''-(4''-amino-1'',2''-oxathiole-2'',2''-dioxide)]-beta-D-pentofurano syl (TSAO) nucleoside analogues retain sensitivity to HIV-1-specific nonnucleoside inhibitors. - Balzarini, J (1993)
We recently reported that a newly discovered class of nucleoside analogues--[2',5'-bis-O-(tert-butyldimethylsilyl)- 3'-spiro-5''-(4''-amino-1'',2''-oxathiole-2'',2''-dioxide)]-beta-D - pentofuranosyl derivatives of pyrimidines and purines (designated TSAO)--are highly specific inhibitors of human immunodeficiency virus type 1 (HIV-1) and targeted at the nonsubstrate binding site of HIV-1 reverse transcriptase (RT). We now find that HIV-1 strains selected for resistance against three different TSAO nucleoside derivatives retain sensitivity to the other HIV-1-specific nonnucleoside derivatives (tetrahydroimidazo[4,5,1-jk][1,4]benzodiazepin-2(1H)-one and -thione (TIBO), 1-[(2-hydroxyethoxy)methyl]-6-phenylthiothymine, nevirapine, and pyridinone L697,661, as well as to the nucleoside analogues 3'-azido-3'-deoxythymidine, ddI, ddC, and 9-(2-phosphonylmethoxyethyl)adenine. Pol gene nucleotide sequence analysis of the TSAO-resistant and -sensitive HIV-1 strains revealed a single amino acid substitution at position 138 (Glu-->Lys) in the RT of all TSAO-resistant HIV-1 strains. HIV-1 RT in which the Glu-138-->Lys substitution was introduced by site-directed mutagenesis and expressed in Escherichia coli could not be purified because of rapid degradation. However, HIV-1 RT containing the Glu-138-->Arg substitution was stable. It lost its sensitivity to the TSAO nucleosides but not to the other HIV-1-specific RT inhibitors (i.e., TIBO and pyridinone). Our findings point to a specific interaction of the 4''-amino group on the 3'-spiro-substituted ribose moiety of the TSAO nucleosides with the carboxylic acid group of glutamic acid at position 138 of HIV-1 RT.